The Reality of Eradicating Corruption in Indonesia; A Comparative Legal Study - Syawaluddin Hanafi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2023)
The purpose of this research is to find out and analyze the reality of eradicating corruption in Indonesia with a comparative legal review between positive law in Indonesia and Islamic law.This research is a descriptive-qualitative legal sociology research that explains the reality of the problem of eradicating corruption in Indonesia. The perspective used in analyzing and finding the ideal construction is Islamic Law with a conceptual approach, historical approach, comparative approach, case approach, and constitutional approach.The findings in this study outline that: First, the reality of corruption that occurs in Indonesia can be seen from the theory of law as a tool of social engineering and law enforcement theory, it is necessary to carry out reforms to encourage reform in society, the emphasis lies on the revision of laws and regulations so that the construction of a new society to be realized in the future through the enactment of laws and regulations in accordance with the needs of the community. Because a good law is a law that is extracted from the norms that live in the community. Second, the purpose of Islamic law is to protect religion, soul, mind, offspring, and property, and to protect the state from corruptive behavior. Efforts to eradicate corruption in the perspective of Islamic law are by providing social sanctions and ta'zir sanctions. prevention efforts can also be carried out by considering cultural aspects and educational aspects, both through formal, non-formal, and informal channels.